2021
DOI: 10.3390/plants10122782
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Symptomatic Detection of Viral Infection in Tobacco Leaves Using PAM Fluorometry

Abstract: Chlorophyll fluorescence imaging was used to study potato virus X (PVX) infection of Nicotiana benthamiana. Infection-induced changes in chlorophyll fluorescence parameters (quantum yield of photosystem II photochemistry (ΦPSII) and non-photochemical fluorescence quenching (NPQ)) in the non-inoculated leaf were recorded and compared with the spatial distribution of the virus detected by the fluorescence of GFP associated with the virus. We determined infection-related changes at different points of the light-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…PAM fluorimetry seems to be a fairly sensitive method for detecting infectious agents inside plants [19,24,51]. The high sensitivity of PAM for pathogen detection at the pre-symptomatic stage has been demonstrated in our previous work [26]. The current results demonstrate that F v /F m , which reflects the structural integrity of PSII, does not change throughout the experimental period (Figures 7 and 8).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…PAM fluorimetry seems to be a fairly sensitive method for detecting infectious agents inside plants [19,24,51]. The high sensitivity of PAM for pathogen detection at the pre-symptomatic stage has been demonstrated in our previous work [26]. The current results demonstrate that F v /F m , which reflects the structural integrity of PSII, does not change throughout the experimental period (Figures 7 and 8).…”
Section: Discussionsupporting
confidence: 73%
“…ΦPSII, qP, NPQ, and qN were recorded both in the light-adapted state and in the transition state-40 s after the actinic light was switched on. The latter, as shown by our previous study, provides the greatest contrast between infected and healthy areas [26]. Images of Fv/Fm, as well as ΦPSII and NPQ in the transition state, along with RGB and fluorescent images, are presented in Figure 7.…”
Section: Detection Of Viral Infection In N Benthamiana Leaves Using T...mentioning
confidence: 55%
See 1 more Smart Citation
“…Ralstonia solanacearum is a devastating disease for tomato seedling; in a study using CFI, F v /F m values between 0.55 and 0.65 were detected, and as a result, the infection was predicted 2 days before visual symptoms [75]. Likewise, CFI was used for the detection of potato virus X (PVX) in Nicotiana benthamiana plants; the study demonstrated that Φ PSII and NPQ parameters in infected areas were different significantly starting from the second day after the detection of the virus, considering the CFI as reliable pre-symptomatic detection a viral infection [76]. Also, the CFI was able to detect biotic and abiotic stress in tomato plants, as was reported by Moustaka et al [77].…”
Section: Cf Tool To Study the Plant-pathogen Interactionmentioning
confidence: 99%
“…The majority of such images were from the first post-inoculation day, when disease severity varied from 0.012% to 0.24%, with a mean of 0.055%. Several studies showed that in pre-symptomatic detection of plant diseases, differences between healthy and diseased plant tissues become statistically significant from the second day after inoculation (Boureau et al, 2002;Grishina et al, 2021). Thus, we proposed to pre-process the dataset in two steps: 1) we applied morphological operations to eliminate corrupted pixels and to uniform lesions if they included small holes; 2) we eliminated images with S≤0.24% .…”
Section: Pre-processing Strategy For a Test Datasetmentioning
confidence: 99%